Supplementary Materials Tree Stands and Liana Community in Royal Belum State Park, Malaysia - Rahmad, Zakaria; Johari, Syafiq; Akomolafe, Gbenga Festus (Borneo Journal of Resource Science and Technology, 2018)
The diversity of lianas and trees were studied in five study sites of 100 x 20 m within the Royal Belum State Park, Malaysia with a view to provide baseline information on their incidence, taxonomy and ecological distributions. The sites include Sungai Kejar, Sungai Papan, Sungai Papan 2, Teluk Gopal and Sungai Kooi with at least 1000 m apart. These plots were further sub-divided into five sub-plots of 20 x 20 m each. Lianas with a diameter at breast height (dbh) ≥ 1 cm and trees with dbh ≥ 10 cm were identified and frequencies of occurrence were determined. Lianas comprising 92 species from 23 families while trees comprising 221 species and 48 families were enumerated. Annonaceae was the richest family of lianas and trees (19 species and 23 species respectively). Connarus (Connaraceae) and Spatholobus (Fabaceae) had the highest number of lianas (six species) whilst Syzygium (Myrtaceae) had the highest number of trees (11 species). There are significant differences in all the diversity indices among the study sites, except between Sungai Papan and Teluk Gopal which were the richest and most diverse in liana species. These two sites also showed high similarity index in liana species (0.50) followed by Sungai Kejar and Sungai Papan 2 (0.37). Sungai Kejar was however observed to have the highest tree species richness. These study sites could be described as very rich with a high diversity of lianas and trees. Although, it is richer in trees than lianas which means that the level of disturbance of the park is very low.